Synthesis and structural characterization of Ni(II) complexes with the chiral CpH(PNMent) tripod ligand. Issue 20 (18th October 2017) - Tsuno, Takashi; Sugiyama, Yu; Brunner, Henri; Bodensteiner, Michael; Lee, Kosei
Abstract: Treatment of NiCl2 with the tripod ligand (LMent, S C )-1 H led to (LMent, S C )-[Cp(PNMent )NiCl] in which the potentially tridentate ligand coordinated to the metal center in a bidentate way via the cyclopentadienyl system and the phosphorus atom. In the presence of NH4 PF6 [(LMent, S C )-[Cp(PNMent )NiCl] readily underwent Cl/PPh3 exchange to give (LMent, S C )-[Cp(PNMent )NiPPh3 ]PF6 . Reaction of (LMent, S C )-[Cp(PNMent )NiCl] with 0.5 eq. of dppe afforded [(LMent, S C )-[Cp(PNMent )Ni]2 dppe](PF6 )2 . (LMent, S C )-[Cp(PNMent )NiPPh3 ]PF6 and [(LMent, S C )-[Cp(PNMent )Ni]2 dppe](PF6 )2 were characterized by NMR and MS spectroscopy, and also by single crystal X-ray diffraction. The cyclopentadienyl ligand of (LMent, S C )-[Cp(PNMent )NiPPh3 ]PF6 shows a distortion intermediate between the ene-allyl and diene types, while the two cyclopentadienyl ligands of [(LMent, S C )-[Cp(PNMent )Ni]2 dppe](PF6 )2 have intermediate and diene distortions, respectively. According to the temperature dependent NMR spectra of (LMent, S C )-[Cp(PNMent )NiPPh3 ]PF6 and [(LMent, S C )-[Cp(PNMent )Ni]2 dppe](PF6 )2 two different conformations of the tether in the Cp(PNMent )Ni system could be frozen out at low temperatures. Abstract :